FILM TOURISM: A CASE STUDY OF SUMEDANG AS SUNDANESE CULTURAL PUSEUR - Denny Nugraha, Novian; Erdhina Adi, Anggar; Budi Haswati, Sri Mharani; Sintowoko, Dyah Ayu Wiwid (Capture : Jurnal Seni Media Rekam, 2022)
As a Sundanese Cultural Puseur (center), Sumedang Regency can arguably increase Local Own-Source Revenues (PAD – Pendapatan Asli Daerah) for the Sumedang Municipal Government. Hence, this artistic study aims to offer a positive identity for Sumedang Regency through film tourism. Specifically, this research employs a practical method to produce a film tourism creation titled “Historical Land of Pasundan.” The results indicate that the visual look of the Sumedang film tourism is quite complex and dynamic, demonstrating the regency’s superior potential, culinary offerings, and indigenous Sundanese culture. Sumedang is specifically labeled as the  Sundanese Culture Puseur partly due to its historical significance and to attract a greater number of domestic and international tourists. This film tourism captures many images containing wide shots, close-ups, and camera movements and hence appears to be very dynamic as a part of the tourism and creative industry’s efforts to recover from the Covid-19 effects.